2019
DOI: 10.5606/tgkdc.dergisi.2019.16324
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of sleeve lobectomy with continuous suture technique in non-small cell lung cancer

Abstract: Bu çalışmada primer küçük hücreli dışı akciğer kanseri nedeniyle bronşiyal sleeve lobektomi uygulanan hastaların ameliyata bağlı komplikasyonları, nüks sıklığı, morbidite, mortalite ve sağkalım oranları ile sağkalım üzerinde etkili değişkenler araştırıldı. Ça lış ma pla nı: Mayıs 2007 ve Kasım 2015 tarihleri arasında kliniğimizde aynı ekip tarafından aynı cerrahi teknik ile ameliyat edilen toplam 85 bronşiyal sleeve lobektomi hastası (80 erkek, 5 kadın; ort. yaş 59.9±8.4 yıl; dağılım, 35-77 yıl) retrospektif o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…They also reported a morbidity of 4.36% and a five-year survival of 62.7% ( 31 ). Yazgan et al reported a five-year survival of 50.9%, a 30-day mortality of 1.2% and a 90-day mortality of 2.4% for a group of 80 patients ( 32 ). In patients undergoing open SL, Mayne et al reported a 5-year survival of 79%, a 30-day mortality of 4.5%, and a 90-day mortality of 6.8% ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…They also reported a morbidity of 4.36% and a five-year survival of 62.7% ( 31 ). Yazgan et al reported a five-year survival of 50.9%, a 30-day mortality of 1.2% and a 90-day mortality of 2.4% for a group of 80 patients ( 32 ). In patients undergoing open SL, Mayne et al reported a 5-year survival of 79%, a 30-day mortality of 4.5%, and a 90-day mortality of 6.8% ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Бронхопластическая лобэктомия также связана с улучшением качества жизни за счёт сохранения паренхимы легких [2][3][4][5][6][7][8][9][10][11]. Однако проспективных рандомизированных исследований, сравнивающих бронхопластическую лобэктомию и пневмонэктомию, не проводилось [12][13][14][15][16][17]. Таким образом, идеальная хирургическая процедура для центрально расположенного НМРЛ оставалась спорной, а показания зависели от каждого случая и, в частности, от оперирующего хирурга.…”
Section: Introductionunclassified